44.1k views
1 vote
Which one is a equivalent expression?

Which one is a equivalent expression?-example-1
User Blmage
by
6.4k points

2 Answers

3 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{7^2\cdot 8^9}{5\cdot 7^6\cdot 8^3}\implies \cfrac{8^9\cdot 8^(-3)}{5\cdot 7^6\cdot 7^(-2)}\implies \cfrac{8^(9-3)}{5\cdot 7^(6-2)}\implies \cfrac{8^6}{5\cdot 7^4}

User Anujith
by
5.7k points
5 votes
Sorry I can’t help I need more information
User Shanker
by
5.8k points